Analysis of Pedestrian Crossing Behavior at Pedestrian Crossings in Shah Alam City, Malaysia - Nasrudin, Na‟asah; Hashim, Habsah; Shakila Khalid, Nurul; Osman, Naimah; Fatimah Hashim, Siti (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is the development of pedestrian crossing choice models in relation to roadway design, traffic flow, and traffic control. This paper also analyzed pedestrian crossing behavior based on pedestrians gender and age group. The data used in the study were collected through a questionnaire survey of 663 pedestrians aged from 13 to 75 years old at eight different areas in Shah Alam City. The areas were selected according to the different types of land uses, such as city centers, commercial districts, and outlying districts. This study has discovered a significant relationship between different age groups and genders of pedestrians in relation to crossing behavior. In terms of age group, this study found that older pedestrians prefer to cross the pedestrian in group compared to younger pedestrians. The majority of pedestrians in the 56-75 age group prefer to walk slowly compared to the majority of the 18-35 age group pedestrians, who prefer to walk a bit fast. There was a significant relationship between the gender and the size of the pedestrian crossing group, which showed that females prefer to cross the pedestrian in the group compared to male pedestrians. In terms of the regularity of crossing at non-designated crosswalks between male and female pedestrians, male pedestrians recorded more „often‟ and „almost always‟ crossing at nondesignated crosswalks compared to female pedestrians. The analysis of pedestrian crossing behavior in urban areas also may assist in understanding the way pedestrians interact with the road and traffic environment, as well as with other pedestrians. It may also help to understand the way they balance the need for comfort and safety at the cost of delays within the framework of existing traffic rules.